2009
DOI: 10.1002/chem.200802538
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Building Blocks Based on the Boradiazaindacene Chromophore: Applications in Fluorescent Metallosupramolecular Coordination Polymers

Abstract: Bright polymers: Fluorescent coordination polymers made up of versatile functionalized bodipy (boron‐dipyrrin) chromophore building blocks, such as that depicted, are described. Polymerization is signaled by changes in fluorescence emission intensity and shifts in peak emission wavelengths.magnified imageWe designed and synthesized novel boradiazaindacene (Bodipy) derivatives that are appropriately functionalized for metal‐ion‐mediated supramolecular polymerization. Thus, ligands for 2‐terpyridyl‐, 2,6‐terpyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…The solubility of BODIPY‐based conjugated polymers can be controlled by functionalization of meso‐phenyl ring with a large variety of substituents at different positions. Very recently, BODIPY‐based conjugated copolymers and co‐oligomers have been reported 29, 30. In this article, we demonstrate the feasibility of the hypothesis to prepare new kind of deep‐red emissive conjugated polymers with triple‐bond connections between BODIPY cores at positions 2 and 6, poly(2,6‐BODIPY‐ethynylene)s bearing dodecyl side chains (Polymers A , B and C ) (Scheme ).…”
Section: Introductionmentioning
confidence: 73%
“…The solubility of BODIPY‐based conjugated polymers can be controlled by functionalization of meso‐phenyl ring with a large variety of substituents at different positions. Very recently, BODIPY‐based conjugated copolymers and co‐oligomers have been reported 29, 30. In this article, we demonstrate the feasibility of the hypothesis to prepare new kind of deep‐red emissive conjugated polymers with triple‐bond connections between BODIPY cores at positions 2 and 6, poly(2,6‐BODIPY‐ethynylene)s bearing dodecyl side chains (Polymers A , B and C ) (Scheme ).…”
Section: Introductionmentioning
confidence: 73%
“…A 1D coordination polymer containing fluorescent BODIPY units exhibited a unique dynamic equilibrium between the polymeric and monomeric state. The β positions of BODIPY was modified with (ethynylphenyl)terpyridyl groups so that the octahedral coordination of the terpyridyl ligands with Zn(II) ions produced a one-dimensional polymer 15 (Figure 9A ) (Bozdemir et al, 2009 ). Upon the addition of the Zn(II) ion, 1 H NMR signals of the ligand were broadened, indicating the formation of the coordination polymer.…”
Section: Infinite and Periodic Supramolecular Architectures And Theirmentioning
confidence: 99%
“…66 The compounds, 2-tetraphenylethene BODIPY 53, 2-ethynylterpyridyl BODIPY 54, and 2-ethynylbipyridyl BODIPY 55 were also synthesized ( Figure 10A) under Pd(0) conditions by the reaction of 2-halo BODIPY with boronic acid/ethynyl compound. 62,67,68 Using the 2-formyl BODIPY 48, a few BODIPY derivatives were synthesized under Schiff base and Knoevenagel reaction conditions and these derivatives were used for sensing various metal ions. For example, compound oxime BODIPY 56 was Figure 10B) and used to sense OClion whereas compound 57 was used for detection of Hg 2+ ion.…”
Section: -Functionalized Bodipysmentioning
confidence: 99%
“…The 2,6dihalogenated BODIPYs 75-77 were prepared by treating appropriate BODIPY with NXS or X 2 (Br 2 , Cl 2 , I 2 ) in CH 2 Cl 2 ( Figure 13A) at room temperature or other slightly varied reaction conditions. 61,62 Recently Wang et al showed that the regioselective dihalogenation at 2,6-positions of BODIPY 2 can be much faster when reactions were carried out in hexafluoro-2-propanol ( Figure 13A) using NXS as the halogen source. 78 The 2,6-diformyl BODIPY 78 was prepared by treating 2-formyl BODIPY 48 under Vilsmeier-Haack reaction conditions ( Figure 13B).…”
Section: 6-difunctionalized Bodipysmentioning
confidence: 99%
See 1 more Smart Citation